(untitled) (Belmont, CA., 1997)
This successful text, now in its seventh edition, offers a biocultural perspective. It integrates basic evolutionary theory, human genetics, coverage of non-human primates, paleoanthropology, and modern population biology to illustrate the physical and behavioral evolution of human beings. New research integrated throughout the text. All Guest Essays are new. A new chapter has been added on Human Growth and Development and timelines have been added before each hominid chapter. Internet resources have been added to the end of each chapter.
Keywords: Physical anthropology,Anthropology, Physical,Nhân chủng học vật lý,Nhân học, vật lý